Inhibition of Rho Kinase Induces Antioxidative Molecules and Suppresses Reactive Oxidative Species in Trabecular Meshwork Cells - Tomokazu Fujimoto; Toshihiro Inoue; Saori Ohira; Nanako Awai-Kasaoka; Takanori Kameda; Miyuki Inoue-Mochita; Hidenobu Tanihara (Journal of Ophthalmology)
Purpose. To investigate the effect of rho kinase inhibitors on oxidative stress in trabecular meshwork (TM) cells. Methods. TM cells were isolated from the eyes of cynomolgus monkeys. Y-27632 and menadione were used to inhibit rho kinase and induce production of reactive oxygen species (ROS), respectively. The cynomolgus monkey array and 12,613 probes were used in DNA microarray analysis, and the affected genes were categorized using gene ontology analysis. The mRNA levels of the target genes were confirmed by real-time RT-PCR. Intracellular oxidative stress was detected using a fluorescent reagent sensitive to ROS. Cell viability was assessed by the WST-8 assay. Results. Gene ontology analysis revealed upregulation of genes involved in antioxidant activity, and upregulation of catalase was confirmed by real-time RT-PCR after 30 min treatment with Y-27632. Production of ROS was increased by menadione, and the effect was partly suppressed by pretreatment with Y-27632. At a lower dose of menadione, Y-27632 stimulated TM cells and significantly increased their viability following menadione treatment compared to control cells. Conclusion. Using microarray analysis, Y-27632 was shown to upregulate antioxidative genes including catalase and partially reduce ROS production and cell death by oxidative stress caused by menadione.